1997
DOI: 10.1038/eye.1997.204
|View full text |Cite
|
Sign up to set email alerts
|

Do transplanted corneal limbal stem cells survive in vivo long term? Possible techniques to detect donor cell survival by polymerase chain reaction with the amelogenin gene and Y-specific probes

Abstract: Leeds SUMMARYPurpose: To investigate donor cell survival following corneal limbal stem cell grafting, which is based on the corneal stem cell model. Methods:We describe the use of the amelogenin gene probe with the polymerase chain reaction (peR) to detect surviving donor cells and report preliminary studies nsing Y-specific DNA probes. Results and conclusions: DNA polymorphisms have a detection limit of 10%. The SRY 'Y-specific' probe has a theoretical detection limit of 1 cell in 10 000. The techniques were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 15 publications
0
10
2
Order By: Relevance
“…We examined five patients at 3–5 years after limbal allotransplantation in order to correlate long term outcomes with survival of donor cells on the ocular surface. This study differs from those we have reported previously10 15 16 in several key aspects. Firstly, multiple microsatellite markers were used to improve the chances of detecting surviving donor cells on the ocular surface.…”
Section: Discussioncontrasting
confidence: 99%
“…We examined five patients at 3–5 years after limbal allotransplantation in order to correlate long term outcomes with survival of donor cells on the ocular surface. This study differs from those we have reported previously10 15 16 in several key aspects. Firstly, multiple microsatellite markers were used to improve the chances of detecting surviving donor cells on the ocular surface.…”
Section: Discussioncontrasting
confidence: 99%
“…Henderson et al 9 investigated a single patient who appeared to have a successful clinical outcome after receiving a limbal allograft along with systemic and topical immunosuppression. They were unable to detect donor cells on the ocular surface beyond 20 weeks after transplantation by using a DNA microsatellite analysis.…”
Section: Discussionmentioning
confidence: 98%
“…The presence of donorderived cells on the recipient ocular surface is used as evidence for estimating the effect of a limbal allograft. [9][10][11][12] However, even after some clinically successful limbal allografts, these cells are difficult to find. 10,12 To further evaluate the efficacy of an immunosuppressant, an animal model is needed to facilitate assessment of the survival of limbal allograft stem cells.…”
mentioning
confidence: 99%
“…Williams et al ( 1995 ) have investigated the survival of donor-derived epithelial cells based on impression cytology after limbal stem cell transplantation (allo), using short tandem-repeat DNA polymorphisms (microsatellites) to distinguish the donor and recipient cells and showed that cells of donor genotype were present over the grafted areas at the time of surgery but were not detected in the central cornea until 12 weeks postoperatively, indicating that repopulation of the epithelial surface from the transplanted limbal stem cells took considerable time while only the recipient-type cells were detected in the grafted eye by 20th week. Henderson et al ( 1997 ) attempted to investigate donor cell survival following corneal Limbal stem cell grafting using amelogenin gene probe (a Y-specifi c DNA probe) with PCR. The same group later (2001) demonstrated that a combination of impression cytology and single cell DNA fi ngerprinting is suitable for detecting transplanted cells after corneal limbal allografting.…”
Section: Clinical Studies Experience Outcome/side Effects Of "Oculamentioning
confidence: 99%